Telephone-operated crime survey for England and Wales, 2020-2021: secure access (Crime Survey for England and Wales, 2023)
The Telephone-Operated Crime Survey for England and Wales (TCSEW) is a telephone victimisation survey, specifically designed to allow for measuring household and personal crime to continue during the coronavirus (COVID-19) pandemic period while face-to-face interviewing was not possible. The face-to-face Crime Survey for England and Wales (CSEW) was temporarily suspended on 17 March 2020 as part of the efforts to minimise social contact and stop the spread of COVID-19. (Standard EUL versions of the CSEW are available at the UK Data Archive under GN 33174, and the Secure Access version is available at SN 7280.) The TCSEW is a shortened telephone-operated version of the CSEW, which asks people resident in households in England and Wales about their experiences of a selected range of offences in the 12 months prior to the interview, as well as a short module specific to the pandemic period relating to their perceptions of crime, the police, and anti-social behaviour. The sample design for the TCSEW differs from the CSEW, as the TCSEW sample is drawn from respondents who had previously participated in the face-to-face CSEW in the last two years and who had agreed to being re-contacted for research purposes. To maximise the sample available, and assure its longevity, the TCSEW was designed to operate as a panel survey, re-interviewing respondents at three-monthly intervals. The TCSEW ran from 20th May 2020 until 31 March 2022, although data are currently available only from fieldwork until March 2021. TCSEW estimates are not directly comparable with those previously published from the face-to-face CSEW. The study data are limited to data from the TCSEW Adult Non-Victim Form. Due to the resource requirements involved, there are no current plans to archive the TCSEW Victim files. In the Non-Victim Form (NVF) each case refers to an individual respondent and includes victims and non-victims. Detailed information on the dataset structure is available in the associated user guide.